Biotic and abiotic features in water-supply ponds of two aquaculture farms covered by macrophytes - Millan, Rodrigo Ney; Sipaúba-Tavares, Lúcia Helena [UNESP] (My University, 2021)
This study assessed the influences of the presence of macrophytes in two shallow water-supply ponds, on the plankton community and water column of a fish farm and a feefishing farm. Samples were collected monthly at both the inlet and outlet of the water-supply ponds over one year. In the fish farm, the water-supply pond was covered by Salvinia auriculata and Eichhornia crassipes, whilst in the fee-fishing farm, the pond was covered by Typha domingensis, both with continuous water flow. In both aquaculture enterprises, nitrate concentrations were reduced by the presence of macrophytes, while other nutrients remained constant. Phytoplankton (e.g. Bacillariophyceae and Zygnematophyceae) had relatively high abundance rates in both systems, with a decreased concentration of Cyanobacteria being observed in the ponds' outlet, especially regarding the free-floating macrophytes in the fish farm. Rotifera and Cyclopoida Copepoda (Thermocyclops decipiens), had the highest rates among zooplanktonic organisms in the water-supply inlets, mostly in the fee-fishing farm with rooted macrophytes. Cladocera and Calanoida Copepoda were found only in the free-floating macrophytes system. The presence of macrophytes favored the phytoplankton assemblage in terms of density and abundance, thus it represents an adequate tool for the maintenance of water-supply ponds in aquaculture enterprises.
Características bióticas e abióticas de dois viveiros de abastecimentento de água para aquicultura cobertos por macrófitas
Keywords: fitoplâncton; macrophytes; macrófitas; parâmetros da água; phytoplankton; water parameters; zooplankton; zooplâncton